Economic Impact of COVID-19 : Implications for Health Financing in Asia and Pacific - Tandon, Ajay; Roubal, Tomas; McDonald, Lachlan; Cowley, Peter; Palu, Toomas; de Oliveira Cruz, Valeria; Eozenou, Patrick; Cain, Jewelwayne; Teo, Hui Sin; Schmidt, Martin; Pambudi, Eko; Postolovska, Iryna; et al. (World Bank, Washington, DC, 2020)
Coronavirus 2019 (COVID-19’s) impact has gone far beyond its direct effect on morbidity and mortality. In addition to adversely impacting non-COVID health care utilization, the pandemic has resulted in a deep global economic contraction due to lockdown policies and declining demand and supply of goods and services. As a result, most countries are experiencing lower levels of gross domestic product (GDP), rising unemployment, higher levels of impoverishment, and increasing income inequality. Some countries are more vulnerable to the economic contagion resulting from COVID-19, including those implementing more stringent lockdowns and those that are more globally integrated due to their dependence on trade, tourism, and remittances. In addition, countries with preexisting conditions of fiscal weakness due to higher dependence on external grant financing, low tax revenues, and large pre-crisis debt levels are struggling to implement countercyclical mitigative fiscal and monetary policies. In addition to declining economic activity, government revenues have declined, government borrowing is increasing, and public debt levels are projected to skyrocket globally. Higher debt levels will likely imply fiscal tightening for years to come. Implications for health financing are potentially dire, dependent in part on the combination of domestic government, external, and out-of-pocket financing for health that is extant across countries. Tentative projections indicate that, in the absence of reprioritization, growth in public spending for health can decline across most low- and middle-income countries in the region, including becoming negative in some cases, risking reversal of gains made toward expanding universal health coverage in recent years. To reduce the likelihood of such a scenario, and with the caveat that protecting levels of financing will not be effective if resources are not used properly to begin with, ministries of health will need to pay careful attention to planning and budgeting - demonstrating where waste can be reduced and efficiency enhanced - and prioritize within their outlays interventions that are the most cost-effective and equitable. At the same time, ministries of finance should improve the adequacy and predictability of outlays for the sector, taking a multiyear programming perspective and include potential additional resources that will be necessary to procure and deliver a COVID-19 vaccine, once an effective one becomes available. In doing so, they should consider augmenting resources via increasing the scope and breadth of health taxes and proactively seeking out debt relief opportunities, especially if these can be tied to efforts to reprioritize health within overall government budgets where this may be necessary. Whereas there is the perception that the health sector has been flooded with new resources to respond to the pandemic, it remains unclear to what extent these have been additional and not a result of reprogramming of outlays from other areas within health. To the extent COVID-19 presents an opportunity, it is one for removing any doubts that health and the economy are inextricably linked, nudging both ministries of health and finance to reevaluate their priorities, accountabilities, and performance to sustain improvements in both population health, including for ensuring pandemic preparedness, and economic performance.